ChemInform Abstract: Gold versus Rhodium: Divergent Reactivity Enabled by the Catalyst. Issue 16 (April 2015) - Winston‐McPherson, Gabrielle N.; Tang, Weiping
Abstract Review: application to the synthesis of important natural product frameworks; 16 refs.